Tactile feeling of textiles: a comparative study between textiles attributes of France, Portugal and Brazil - Nagamatsu, Naomi (2017)
[Excerpt] The sensorial comfort is the result of a complex series of sensory stimuli between the fabric and human skin when wearing or touching a garment. The sensory comfort is not influenced by the thermal equilibrium but by the feeling that the clothing provides the user with when in contact (mechanical or thermal) with the skin: the touch. Tactile properties are quantitatively evaluated through adaptations of sensory analysis methods, much exploited by the food and cosmetics industries. This assessment is the descriptive result of psychological and physiological responses of individuals. Before the evaluation of the textile comfort process it is necessary to develop descriptive terminologies of attributes that best define the characteristics of a product. Development of the attributes is made by a panel of selected volunteer assessor. Researchers from France (2004), Portugal (2011) and Brazil (2016) developed a set of touch attributes, which were classified and grouped. They followed the same methodology: ISO 11035, ISO 8586 and the Descriptive and Quantitative Analysis Method. Thus, the present study compares the textile quality attributes developed by these researchers. [...]